Slender thin‐walled box columns subjected to compression and bending - Pavlovčič, Luka; Froschmeier, Bernadette; Kuhlmann, Ulrike; Beg, Darko (Journal of Civil Engineering and Management, 2010)
This paper deals with tests on slender thin‐walled box columns, susceptible to instability of both types: to global Euler buckling as well as to local buckling of steel plates. Eight full‐scale tests were carried out with different global slenderness of welded and cold‐formed columns subjected to centric and eccentric compression. For the purpose of profound numerical simulations of tests, material properties were also tested, and the initial column geometry and residual stresses were carefully measured. The results of FEA simulations show good agreement with the test results. On verified numerical model the influence of different initial imperfections was studied. First Published Online: 24 Jun 2011